“Shopping trem”: uma análise das atividades de trabalho informal no interior das composições da Linha 8 (Diamante) da CPTM - Capelli, Rodrigo Dionisi (2017)
The present dissertation aims to analyze the commerce situation in the wagons of the train compositions crossing the West Zone of São Paulo Metropolitan Region, foccusing on Line 8 (Diamond), which is a part of CPTM (Companhia Paulista de Trens Metropolitanos) structure. Considering that, a historical contextualization of the phenomenon (informal work) in which my object is inserted was developed. The analysis of the literature addressing the subject as to its concepts, as well as the field observation of the commerce inside the compositions in different days and times, substantiate this study to faithfully de-scribe the informal work carried out, which despite the illegality, represents the sub-sistence of those individuals. The relation of those illegal activities and the society in a general perspective was approached, based on the field observations and on the interviews of a selected group of workers. The data collected underlie the description and analysis of the set of relations concerned as the objective aimed to this dissertation